2020
DOI: 10.1002/er.5309
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of rhombic‐driven and crank‐driven beta‐type Stirling engines

Abstract: This work aims to compare beta-type Stirling engine performance [ground power unit]) driven by rhombic and crank mechanisms. A modified non-ideal adiabatic model accounting for different frictional and thermal losses was adopted in this study. After validating the current model with engine experimental data, different scenarios of operating conditions including heater temperature, cooler temperature, charge pressure and engine speed were investigated. The results revealed that rhombic drive mechanism generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…However, these engines only run under conditions of high‐temperature difference and high charge pressure. Alfarawi 15 investigated the differences in the performance of a GPU‐3 β ‐type Stirling engine driven by a rhombic or a crank mechanism. They found that at a lower hot‐end temperature of 300°C and lower charge pressure of 10 bar, both mechanisms cannot even drive the engine (producing negative work).…”
Section: Introductionmentioning
confidence: 99%
“…However, these engines only run under conditions of high‐temperature difference and high charge pressure. Alfarawi 15 investigated the differences in the performance of a GPU‐3 β ‐type Stirling engine driven by a rhombic or a crank mechanism. They found that at a lower hot‐end temperature of 300°C and lower charge pressure of 10 bar, both mechanisms cannot even drive the engine (producing negative work).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the fluid friction associated with the flow through the heat exchangers and manifolds results in a pressure drop through these components. This consequently has an effect of reducing the power output of the engine, so-called pumping loss [14], [33]. Generally, the pressure drop through the heater, cooler and regenerator is calculated using empirical correlations for the friction coefficient.…”
Section: Pumping Lossmentioning
confidence: 99%
“…Rejeneratör, enerji depolama görevi yapan gözenekli bir ısı eşanjörüdür. Stirling motorunda iş akışkanının çevrimde dolaşımı, krank miline bağlı pistonların sinüzoidal hareketiyle sağlanır [6]. Stirling motorları, iş akışkanının geçiş yolları, hareket iletim mekanizmaları, güç pistonu, yer değiştirme pistonu ve rejeneratörün düzeni ile yerlerinin çeşitliliğine göre farklı türlere sahiptir.…”
Section: Giriş (Introduction)unclassified